CURRICULUM MANAGEMENT STRATEGY AS EFFORTS IMPROVING QUALITY EDUCATION - Yossita Wisman (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The formulation of the problem in this thesis is how the problem of curriculum management in an effort to improve the quality of education in di Madrasah Tsanawiyah Negeri Samba Katung Kecamatan Katingan Tengah and how the curriculum management strategy in an effort to improve the quality of education in Madrasah Tsanawiyah Negeri Samba Katung Kecamatan Katingan Tengah.Research that the authors do is include qualitative descriptive research and in collecting data authors using interviews, observation and documentation. As for the analysis, the authors use descriptive qualitative analysis techniques, namely in the form of data written or oral from people and behavior observed so that in this case the author seeks to conduct research that is actually.The result of the research that the writer do knows that the problem of curriculum management in improving the quality of education in di Madrasah Tsanawiyah Negeri Samba Katung Kecamatan Katingan Tengah is the lack of time allocation, the number of students in one class is too much, and the lack of educational infrastructure facilities. Strategies undertaken in improving the quality of education include: Management of learning activities in subjects is organized entirely by madrasah. Madrasahs can add or change the allocation of subject time according to the needs of students, madrasas or foundations. One lesson is held for 40 minutes. Carry out remidi activities, Implementation of teaching and learning process is not only done in class but can also be in the library and in the porch of the mosque. Procurement of manuals for teachers and students. Hold meetings or deliberations for each otherexchanging information on teaching methods as well as other matters relating to the advancement of science and technology. Giving subjects English and Arabic language using the laboratory. Conducting study groups, Conducting lessons and try out to face national examinations for the third grade. Introduce information and communication technology according to the ability such as computers. The strategy to improve the quality of education is not only limited to the curriculum management but also from another aspect of improving the professionalism of teachers by taking part in MGMP activities, seminars and others.